2015
DOI: 10.14238/pi55.3.2015.04
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of soil-transmitted helminthiasis-infected and uninfected children

Abstract: Background Soil-transmitted helminth (STH) infections remain a public health problem in developing countries. Their prevalence is particularly high in rural areas with people of low socioeconomic level. A single or mixed STH infection rarely causes death, but can affect nutritional status, growth, cognitive development and human health, especially in children. Objective To compare the nutritional status of STH-infected and uninfected children. Methods This cross-sectional study was conducted in June 2010 in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…5 This is due to poor immunity and lack of awareness to live clean and healthily. 6 Especially in Bali, the prevalence of STH infections in rural areas is still high. In the village of Telaga, the prevalence of intestinal worm infections was reached 68.41% of 93 public elementary school students of Telaga I and 83.87% of 72 elementary school students in Telaga II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This is due to poor immunity and lack of awareness to live clean and healthily. 6 Especially in Bali, the prevalence of STH infections in rural areas is still high. In the village of Telaga, the prevalence of intestinal worm infections was reached 68.41% of 93 public elementary school students of Telaga I and 83.87% of 72 elementary school students in Telaga II.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to increase the effectiveness of helminthiasis, valid data is needed regarding the incidence of helminthiasis, and education on the prevention of intestinal worm infections and administration of helminthic drugs to infected students is necessary. [5][6][7][8] Based on the exposition above, this study is to find out the prevalence and risk factors which contribute to the incidence of STH infection in elementary school children in Ngis Village, Karangasem District, Bali.…”
Section: Introductionmentioning
confidence: 99%
“…this causes chronic growth disorders [15]. (22.9) fection is, the lower a child's nutritional status will be (p-value = 0.0001) [35]. In the study conducted by Ahmed et al, significant evidence was found that STH infections cause stunted growth, and this was observed in as much as 31.3% of the study participants (p-value = 0.006).…”
Section: Discussionmentioning
confidence: 95%
“…Parasite helminthes (worms) that infect humans belong to two phyla, phylum Platyhelminthes (flat worms) and phylum nematode (round worms). The main soil transmitted nematode species are Ascaris lumbricoides, Trichuris trichiura and the hookworms (Necatoramericanus and Ancylostoma duodenal) [1,2].…”
Section: Introductionmentioning
confidence: 99%